Environmental Insurance as a factor in the prevention of environmental risks: Theory and Practice. (Journal of actual problems of jurisprudence, 2016)
The article discusses the environmental insurance and its role in ensuring environmental safety. The article also discussed in detail the international experience to determine the amount of damages. A special place is occupied with the jurisprudence. The lack of clear mechanisms to determine the extent of damage is a major problem in this direction. Certainly, it is important to also consider the interests of the business community.Environmental risks that lurk in the sphere of nature certainly require the definition of clear mechanisms to ensure environmental safety.
Keywords: damage assessment; environmental risks; environmental safety